Role of Management Education in creating future Business Leaders - Throat, Pooja; Sharma, Dr. Aarti (The journal of contemporary issues in business and government, 2022)
To be competitive the business needs to be innovative and proactive. Business needs leaders who are competent enough to perform at par. However, the industry tries to identify the required talent essential for making a business successful, especially in higher positions from B-School. The role of higher education is vital over here. Developing the right qualities, skills, and values among management students is the first and foremost responsibility of B-schools. Management education is still trying to bridge this gap of the talent, required by the industry to be sustainable in the VUCA world. This study tries to identify students’ perceptions of the degree of knowledge, skills, and values as part of holistic education are imparted and the challenges identified by the industry experts in the dissemination of knowledge and skills. Parameters for knowledge skills and Values are identified based on the literature available. Primary data is collected from 75 respondents including industry experts, and students to identify the gap. Two sets of questionnaires were prepared. Quantitative and qualitative data are used for analysis. For qualitative data, descriptive statistics are used. The study found that knowledge related to current Affairs and business scenarios is disseminated very frequently but less focus is on self and social awareness as well as Knowledge of Information technology. the skills are concerned few skills are imparted effectively but essential skills like managing failures and emotional stability.